Decreased expression of stomatin predicts poor prognosis in HER2-positive breast cancer. Issue 1 (December 2016) - Chen, Chin-Yau; Yang, Chih-Yung; Chen, Yen-Chung; Shih, Chia-Wen; Lo, Su-Shun; Lin, Chi-Hung
Abstract Background Human epidermal growth factor receptor-2 (HER2) is a transmembrane tyrosine kinase receptor that is overexpressed in 25 to 30 % of human breast cancers and is preferentially localized in lipid rafts. Stomatin is a membrane protein that is absent from the erythrocyte plasma membrane in patients with congenital stomatocytosis and is the major component of the lipid raft. Results In a total of 68 clinical cases of HER2-positive breast cancer, the absence of stomatin expression was associated with a decreased 5-year survival (65 % vs. 93 %, p =  0.005) by survival analysis. For stage I-III HER2-positive breast cancer, the absence of stomatin expression was associated with a decreased 5-year disease-free survival (57 % vs. 81 %, p =  0.016) and was an independent prognostic factor by multivariate analysis. Negative stomatin expression predicts distant metastases in a hazard ratio of 4.0 (95 % confidence interval from 1.3 to 12.5). Conclusions These results may suggest that stomatin is a new prognostic indicator for HER2-positive breast cancer.